Analgesia Preventiva, ao Teste do Formol, por Terapia Laser em Ratinhos - Daniel Pozza (2007)
The present research assessed the analgesic effect of the laser therapy in healthy tissues of 10 mice divided into two groups: - L: red laser irradiation (665 nm, 30 mW, 10 J/cm2, 334 s). - C: control laser irradiation (334 s). After laser therapy formalin solution was injected on the same paw, the animal was placed in a transparent box and observers recorded the paw rose time during 30 minutes. The results showed statistical difference and red laser presented better results in all times.